PENINGKATAN KEMAMPUAN KOMUNIKASI SISWA MELALUI PEMBELAJARAN MATEMATIKA REALISTIK DENGAN BERBANTUAN GOOGLE CLASSROOM - Supartik Supartik; Laili Habibah Pasaribu (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
The purpose and problem formulation of this research is to find out whether realistic mathematics learning assisted by google classroom can improve students' communication skills. This research method is quantitative descriptive research. The sample in this study were 25 students who were taken from the total population of data and could represent the entire population with the sample collection technique, namely the random sampling technique. The results of this study were tested with a simple correlation test resulting in the calculated F value of 12,827 at the sig level 0.002 which means significant. From the distribution list F with dk numerator 1 and dk denominator (n-2) = 23 at the real level α = 0.05, obtained F table = 4.28. Then it is concluded that there is a significant increase provided that the value of F count > F table = 12.827 > 4.28. By obtaining this, the researchers concluded that realistic mathematics learning (PMR) assisted by google classroom can improve students' communication skills.